Assessing the relationship between maintenance performance characteristics and a conducive school environment / Nor Amin Mohd Radzuan - Mohd Radzuan, Nor Amin (2021)
School maintenance performance is directly associated with providing a conducive school environment (CSE) for the teaching and learning process. It is well acknowledged that many scholars have discussed school maintenance performance. However, school maintenance performance persists, and it is viewed as a challenge to meet teaching and learning demands. In addition, CSE has long been a topic of discussion among Malaysian scholars and stakeholders. It is seen as a persistent and prolonged issue. Therefore, this research aims to develop a maintenance performance framework to assess the relationship between identified MPCs and CSE. Three objectives were set for the study. The first research objective is to identify the School Administrator (SA)'s attributes in maintenance performance for the National Religious Secondary School (NRSS). The second research objective is to examine the relationship between the MPCs for the NRSS and CSE. Finally, the third research objective is to develop a maintenance performance framework for the NRSS towards CSE. This research specifically focused on the entire 60 NRSS as the case studies throughout Malaysia. This study employed the philosophy of positivism with a deductive approach and survey strategies. The conceptual framework is developed based on SERVQUAL theory and an extensive review of the existing literature. The findings from this phase laid the initial MPCs that will be further investigated in the second phase of this study. The main data collection method is through a questionnaire distributed during the survey. The data were collected from the entire NRSS in Malaysia. The data were initially analysed using Statistical Package for Social Science (SPSS 21) for factor analysis and Structural Equation Modelling (SEM-PLS 3.0) to achieve this study's second and third objectives. The final Maintenance Performance Framework as the main outcome of this study was produced based on the findings from the literature and further analysed using SPSS and SEM-PLS. The framework concludes that Behaviour (BHV), Leadership (LED) and Safety (SAF) have a significant relationship. Comparatively, Complaint Management (COM), Service Delivery (SER) and Islamic Work Ethic (TWE) minimally affect the developed framework. The findings of this study indicated that Maintenance Performance Characteristics (MPCs) is essential in creating a CSE. As an implication, this final framework could potentially be a guide for policymakers, practitioners and scholars. The developed framework will assist in improving school maintenance performance at large. These findings have contributed to filling the knowledge gap by explaining the MPCs and relationship to provide a CSE. Since the study in this area is still evolving, an overview of the MPCs can create awareness and enhance knowledge among relevant stakeholders.